2017
DOI: 10.24953/turkjped.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Conventional insulin pump therapy in two neonatal diabetes patients harboring the homozygous PTF1A enhancer mutation: Need for a novel approach for the management of neonatal diabetes

Abstract: Kurnaz E, Aycan Z, Yıldırım N, Çetinkaya S. Conventional insulin pump therapy in two neonatal diabetes patients harboring the homozygous PTF1A enhancer mutation: Need for a novel approach for the management of neonatal diabetes. Turk J Pediatr 2017; 59: 458-462. The enhancer of PTF1A mutation causes developmental defects of the pancreas. This condition can result in insulin-requiring diabetes and exocrine pancreatic insufficiency. We report two patients with diabetes mellitus harboring the homozygous PTF1A enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This phenotype and epigenetic data suggested that this enhancer is pancreas specific and functional analysis demonstrated that the base substitutions disrupted enhancer activity by abolishing transcription factor (FOXA2 and PDX1) binding ( 15 ). After the initial report, 8 further cases have been published ( 16-18 , 26 , 27 ). Overall these cases appear to be more common than those with biallelic truncating PTF1A variants, likely due to the higher survival rate resulting from the lack of severe neurological features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenotype and epigenetic data suggested that this enhancer is pancreas specific and functional analysis demonstrated that the base substitutions disrupted enhancer activity by abolishing transcription factor (FOXA2 and PDX1) binding ( 15 ). After the initial report, 8 further cases have been published ( 16-18 , 26 , 27 ). Overall these cases appear to be more common than those with biallelic truncating PTF1A variants, likely due to the higher survival rate resulting from the lack of severe neurological features.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the long-term growth outcome in patients with distal enhancer PTF1A mutations have so far been scarce. In some case reports of patients with enhancer mutations, catch-up growth in the infancy period has been reported ( 16 , 17 , 26 , 27 ). Nevertheless, the majority of these reports did not provide a long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Among the subgroups of NDM, TNDM is characterized by self limited hyperglycemia, which lasts for a median of 12 weeks and completely resolves by the age of 18 months 13,14) . TNDM accounts for approximately 45% of all NDM cases, PNDM accounts for most of the remaining 55%, and syndromic NDM constitutes 10,15) . Overexpression of the imprinted genes at chromosome 6q24 as well as mutations in ZFP57 and HNF1B have been re ported to be responsible for TNDM.…”
Section: Discussionmentioning
confidence: 99%
“…It rapidly switches off when the risk of hypoglycemic episodes is anticipated. Never theless, inconsistencies of appetite and feeding schedule and fre quent infection of the needle insertion sites are factors that pose difficulties in treating diabetes during the neonatal period 10) .…”
Section: Case Reportmentioning
confidence: 99%
“…Rapid‐acting insulin can be diluted to 1/10 (U10) or U50 with sterile NPH diluent and stored for 1 month 67 for use in pumps for infants or very young children. Insulin diluted in a 1/5 ratio (U20 insulin; 20 units/ml) has been used successfully during automated insulin treatment in young children (3–6 years old) with T1D 68–72 . Dosing errors with unconventional insulin concentrations can be serious.…”
Section: Insulin Formulationsmentioning
confidence: 99%